Fundamentalisme Agama dan Dahaga Spiritualitas Manusia Modern - Triyanta, Agus (Unisia, 2016)
Fundamentalism, as has been proved by many researchers, does not only occur in Islam. Almost all of religion across the world may be potential to be locus of fundamentalism. The Issue of fundamentalism is getting popular recently. This because there are a lot of political cases and social unrests relate with fundamentalism behavior . Here, are examired factors that cause the rise of fundamentalism, especially relates with the need for spirituality among modern people.